2013
DOI: 10.1016/j.jtcvs.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Cold agglutinins in patients undergoing cardiac surgery requiring cardiopulmonary bypass

Abstract: All patients with CA/cold hemagglutinin disease at the Mayo Clinic College of Medicine safely underwent cardiac surgery without major adverse morbidity or mortality. Patients with CA but without evidence of cold hemagglutinin disease can safely undergo normothermic cardiopulmonary bypass at 37°C and warm cardioplegia without further testing. Patients with cold hemagglutinin disease should undergo laboratory testing including CA titers and thermal amplitude and hematology consultation before cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 26 publications
1
63
0
1
Order By: Relevance
“…Cold agglutinins are autoantibodies that agglutinate red blood cells at low temperatures, leading to haemagglutination and haemolysis 1–11. They are generally of no clinical significance 1–3 5 6 8 10 11.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cold agglutinins are autoantibodies that agglutinate red blood cells at low temperatures, leading to haemagglutination and haemolysis 1–11. They are generally of no clinical significance 1–3 5 6 8 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…They are generally of no clinical significance 1–3 5 6 8 10 11. However, when people who have cold agglutinins in their blood undergo cardiac operation under hypothermia and cold cardioplegia, they can experience complications 1 2 4 6 7 10 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate screening with CA titers and thermal threshold has been recommended for patients undergoing cardiac surgery who are suspected to be at risk. 1 However, the incidence of cold agglutination syndrome was found to be 0.3% among 14,900 patients undergoing cardiac surgery with CPB who were all screened with CA titers. Jain et al reported that the surgeons altered cardiopulmonary bypass management by avoiding hypothermia in only one-third of the identified patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because cardiopulmonary bypass (CPB) can involve deliberate hypothermia of the systemic and coronary circulations, the adverse sequelae of CA have been feared and reported under such conditions. The authors present a case of successful perioperative management of a patient in whom CA activation was diagnosed after the initiation of CPB for coronary artery bypass grafting (CABG) and aortic valve replacement (AVR).…”
mentioning
confidence: 99%